Medium constituents mediated engineering for size and shape tuning of gold nanocrystallites - Suresh, Anil K.; Vijay, Veena; Hameed, Bahrudeen S.; Ramasamy, Sureshkumar; Sakthivel, Natarajan (Journal of Industrial and Engineering Chemistry, 2017)
The current investigation introduces the utilization of cell culture mediums as a novel source for the one plot synthesis as well as stabilization of metal nanoparticles. By varying the medium constituents we could control the size and shape distributions of the gold nanoparticles. Nanospheres of diameter 24 +/- 6 nm and 19 +/- 5 nm were produced using DMEM and M199 mediums respectively, nanoneedles of 150 +/- 50 nm using RPMI medium and nanoflowers of 60 +/- 25 nm using IMDM medium, with an overall yield of 91 +/- 2%. A remarkable decrease in the reaction duration (<3 min) was noted, irrespective of the growth mediums used. Fourier transform infrared spectroscopy and zeta potential measurements revealed them to have a common protenacious encapping agent with different overall surface charges of -23 +/- 3, -21 +/- 1, -24 +/- 2, and -20 +/- 1 mV for Au@DMEM, Au@RPMI, Au@IMDM and Au@M199 respectively. X-ray diffraction confirmed the purity and crystallinity of the particles with Bragg peaks at (111), (200), (220) and (311) for gold nanocrystals. This approach could lead to the creative utilization of novel eco-friendly sources for the production and size/shape control of nanoparticles. Moreover, the adopted methodology is absolutely green, robust and facile, offering new insights for sustainable synthesis for various biomedical and engineering applications. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.